Enhancement in the photocatalytic and optoelectronic properties of erbium oxide by adding zinc oxide and molybdenum. Issue 12 (15th June 2023) - Shabbir, Muhammad Talha; Hussain, Tayyab; Shakir, Sehar; Anwar, Mustafa; Khoja, Asif Hussain; Nawaz, Syed; Satti, Aamir Naseem
Abstract: Rare earth metals like erbium oxide (Er2 O3 ) show outstanding photocatalytic properties. However, its high recombination rate and low surface area limit its performance. Therefore, various metal oxide composites with Er2 O3 have been reported to improve their photocatalytic and optoelectronic properties. In this study, a composite of Er2 O3 and zinc oxide (ZnO) was synthesized using the sol-gel combustion method to enhance its surface area. Moreover, molybdenum (Mo) was loaded on the matrix to suppress the charge recombination. The detailed characterizations were conducted by employing X-ray Diffraction (XRD), Raman Spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Brunauer–Emmett–Teller (BET) analysis, Photoluminescence (PL) spectroscopy and UV–Vis spectroscopy. BET analysis revealed the enhancement in surface area by adding ZnO and Mo (from SBET = 29.07 m 2 /g to SBET = 45.71 m 2 /g). Additionally, the loading of Mo enhanced the immobilization of carriers that facilitate the photooxidation process and suppressed the electron-holes recombination (from 800 counts to 100 counts) as confirmed by the PL spectroscopy. Photocatalytic studies were comparatively analyzed by degradation of textile dye named methylene blue (MB). The efficiency of Er2 O3 improved by up to 80% by adding the ZnO and Mo. The composite of Er2 O3 with ZnO and loading of Mo, not only improved the photocatalytic properties but also improved the electrical properties of the Er2 O3 (σ = 4.4 × 10 −4 Sm −1 to σ = 5.1 × 10 −4 Sm −1 ) as confirmed by the Hall Effect. Due to enhancement in properties, the proposed material can be rendered as one of the most suitable candidates for optoelectronic applications.